Psoriasis, biological drugs and Coronavirus Disease 2019: Real life experience of two Italian provinces - Martina Vispi; Teresa Corradin; Camilla Peccianti; Luca Feci; Laura Casini; Chiara Pisani; Susanna Fabbroni; Paola Corsetti; Margherita Croatto; Michele Pellegrino (PAGEPress Publications, 2020)
On January 30, 2020, World Health Organization (WHO) stated that a new coronavirus disease outbreak [COronaVIrus Disease - 19 (COVID-19)] was an international public health emergency. Many news, often fake ones, about the derived pandemic rapidly spread along the media, thus leading many dermatological patients to identify as "risk category" and sometimes discontinue treatments by themselves. The Dermatology Units in Grosseto and Pordenone simultaneously carried out a data collection by remote-conducted visits, evaluating the incidence of COVID-19 in psoriatic patients. Only 1 patient (close contact of a case) as part of the psoriasis analyzed group was tested and turned out to be positive for SARS-CoV-2, developing no symptoms during the observation period. The collected information may suggest that psoriasis, biotechnologically treated or not, cannot promote or aggravate the clinical trend of the SARS-CoV-2 infection, hence stopping systemic therapy in negative or clinically free SARS-CoV-2 patients is not recommended in general.